Optimization of Gating system in semiconductor packaging - F.Y. Lim; S. Abdullah; I. Ahmad (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.